2017
DOI: 10.1108/jsm-09-2016-0339
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence in front-line/back-office employee relationships

Abstract: Purpose This paper aims to undertake a simultaneous assessment of interdependence in the behaviours of front-line and back-office employees and their joint effect on customer-related organisational performance. It also tests for a moderating influence of the emotional intelligence of front-line salespeople and back-office employees. Design/methodology/approach The sample comprises 105 front-line sales employees and 77 back-office employees. The customer-related organisational performance data come from a UK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 103 publications
0
27
0
Order By: Relevance
“…From the study of the post purchase process, a satisfactory purchase experience is a crucial prerequisite to repeat purchases or customer loyalty (Kearney et. al., 2017;Oliver, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…From the study of the post purchase process, a satisfactory purchase experience is a crucial prerequisite to repeat purchases or customer loyalty (Kearney et. al., 2017;Oliver, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Emotional intelligence also weakens the positive influence of role ambiguity on salesperson emotional exhaustion. Kearney et al (2017) To assess (1) the behavioral interdependence between frontline and back-office employees and their joint effect on customer-related organizational performance and (2) to test the moderating effect of the emotional intelligence of frontline salespeople and back- There is an inverted U-shaped relationship between sales effort and relational performance, though this relationship becomes a positive linear one when the salesperson has higher levels of emotional intelligence. Briggs, Kalra, and Agnihotri, (2018) To understand the role of the salespeople's ability to appraise emotions and its impact on jobrelated consequences in a transaction-oriented setting Survey in an emerging market on 152 matched pairs of salespeople and supervisors working in a financial services organization Emotion appraisal ability gives rise to emotional exhaustion of the salesperson but improves his or her customer service.…”
Section: Notesmentioning
confidence: 99%
“…Santos et al (2015) and others suggested that service employees' jobs traditionally require a high level of interpersonal contact with internal and external clients (Kulik et al, 2009;Lee and Ok, 2012). Moreover, the frequency of such interactions has been shown to have a substantial impact on employees' abilities and their use of emotions (Kearney et al, 2017;Mustafa et al, 2016). Jung and Yoon (2012) showed further evidence that among hotel employees the type of job (eg back of house (BOH) or front-of-house (FOH)) attenuated the relationship between EI and OCB.…”
Section: Frequency Of Customer Contact As a Moderator In The Ei-ocb Rmentioning
confidence: 98%
“…There has been a growing recognition among scholars of the importance of emotional intelligence (EI) (Mayer and Salovey, 1997) as a predictor of employee OCB (Miao et al, 2016;Ramachandran et al, 2011;Turnipseed, 2017;Turnipseed and Vandewaa, 2012). EI is particularly relevant for front-of-house hotel employees as the very nature of their roles require emotionally based interactions with customers, thus requiring them to understand and manage not only their own emotions but those of the customers (Carmeli and Josman, 2006;Kearney et al, 2017).…”
Section: Theoretical Background 21 Organisational Citizenship Behavimentioning
confidence: 99%